Video gamers - Crawford, Garry; T&F eBooks (Milton Park, Abingdon, Oxon ; New York : Routledge, 2012)
"Video gaming is economically, educationally, culturally, socially and theoretically important, and has, in a relatively short period of time, firmly cemented its place within contemporary life. It is fair to say, however, that the majority of research to date has focused most specifically on either the video games themselves, or the direct engagement of gamers with a specific piece of game technology. In contrast, Video Gamers is the first book to explicitly and comprehensively address how digital games are experienced and engaged with in the everyday lives, social networks and consumer patterns of those who play them. In doing so, the book provides a key introduction to the study of gamers and the games they play, whilst also reflecting on the current debates and literatures surrounding the virtual world"--
1. Studying video games -- 2. Understanding video gameplay -- 3. Video gamers as audience -- 4. Who plays video games? -- 5. Key aspects of video gameplay -- 6. Conceptualizing video gamer culture -- 7. Video gamer productivity -- 8. Video gaming and everyday life.
Includes bibliographical references (p. [163]-179) and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Video games; Video games -- Social aspects; Electronic books